Mechanism for Providing Retail Financial Services in Uzbekistan - ugli, Askarov Sarvar Anvar (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In this article, banks are in the process of digital transformation Problems and current situation in improving retail banking services are analyzed. In particular, in the transformation of the banking system of Uzbekistan, the revision of the bank structure and the optimization of the bank's service processes, the one-step lending system through underwriters and the management of personal funds for users are the most important. comments on the applications. The results of this study are important in studying the factors influencing the development of retail banking services and eliminating problematic situations.